Large renal arteriovenous fistula treated by embolization: a case report - VT Duc, PhD, MD; NQT Duong, MD; NT Phong, MD; NH Nam, MD; DA Quoc, MD; TTQ Cuong, MD; NH Huy, MD; TL Duy, MD; PC Chien, MD (Radiology Case Reports, 2021)
Renal arteriovenous fistula (RAVF) is an uncommon vascular malformation of the kidney, which can be congenital, acquired or idiopathic. Although most patients are asymptomatic, RAVF can lead to hypertension, heart failure, renal insufficiency, hematuria, and progressive increase in size of renal vessels. Diagnosis is aided by radiological studies, with digital subtraction angiography as a gold standard. Besides, ultrasound with color Doppler and computed tomography angiography are noninvasive imaging techniques and can be useful for planning the treatment. A large fistula are generally treated by nephrectomy. Intervention can ameliorate the hemodynamic effects of high flow and to preserve the renal parenchymal function. Although endovascular therapy may be challenging due to the large size and high flow of fistula, this report describes a case of huge RAVF was successfully treated by embolization instead of surgery.